2020
DOI: 10.1016/j.celrep.2020.107892
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Receptor TIGIT Expressed on Tim-1+ B Cells Regulates Tissue Inflammation

Abstract: Highlights d Tim-1 + B cells are required for maintaining immune tolerance d Tim-1 + B cells differentially express TIGIT and other coinhibitory molecules d B cell expression of TIGIT and many other regulators requires Tim-1 signaling d B cell TIGIT expression is preferentially required for maintaining CNS tolerance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 29 publications
(45 reference statements)
1
64
1
Order By: Relevance
“…Notably, there was not a major overlap between IL‐10 and TIGIT, which were expressed by distinct populations of TIM‐1 + B cells. TIM‐1 was also found to negatively regulate B cell expression of inflammatory cytokines such as IL‐6, IL‐12, and IL‐23, perhaps enforcing the regulatory balance between Bregs and Beffs 26 . Taken together, these data suggest that while TIM‐1 may not be specific for IL‐10 per se, it may be specific for Bregs that use a variety of mechanisms of action.…”
Section: Regualtory B Cells In Micementioning
confidence: 92%
See 3 more Smart Citations
“…Notably, there was not a major overlap between IL‐10 and TIGIT, which were expressed by distinct populations of TIM‐1 + B cells. TIM‐1 was also found to negatively regulate B cell expression of inflammatory cytokines such as IL‐6, IL‐12, and IL‐23, perhaps enforcing the regulatory balance between Bregs and Beffs 26 . Taken together, these data suggest that while TIM‐1 may not be specific for IL‐10 per se, it may be specific for Bregs that use a variety of mechanisms of action.…”
Section: Regualtory B Cells In Micementioning
confidence: 92%
“…Thus, TIM‐1 regulates an array of potentially inhibitory molecules and may link different “types” of Bregs that utilize distinct mechanisms. Indeed, specific deletion of TIGIT in B cells resulted in spontaneous EAE‐like paralysis and multi‐organ inflammatory cell infiltration, though less severe than that seen in TIM‐1‐BKO mice 26 . Notably, there was not a major overlap between IL‐10 and TIGIT, which were expressed by distinct populations of TIM‐1 + B cells.…”
Section: Regualtory B Cells In Micementioning
confidence: 97%
See 2 more Smart Citations
“…[105][106][107] Similarly, it was recently reported that anti-inflammatory B cells controlled by the commensal flora migrate the gut to the CNS to limit tissue pathology in MS. 108 Interestingly, AHR controls B-cell anti-inflammatory activities. 109,110 Moreover, AHR controls the differentiation and stability of intestinal Tregs, 47,85 and oral administration of the AHR agonist ITE increases the myelin-reactive Treg/Teff ratio and suppresses EAE. 85 These findings suggest that AHR signaling contributes to the anti-inflammatory effects of the commensal flora not only in the gut but also in other tissues, such as the CNS.…”
Section: Modulation Of Inflammation In the Central Nervous System (Cns)mentioning
confidence: 99%